2012
DOI: 10.1111/j.1600-0528.2012.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative performance of different dental professional groups in screening for occlusal caries

Abstract: Even with minimal training, different members of the dental team show the potential to screen for occlusal caries to a similar standard as primary care dentists. This requires further testing in vivo, but has important implications for the productivity and design of the future dental workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…22,25 There is evidence for the use of DCPs and clinicians other than GDPs to detect caries and to screen for oral cancer. [26][27][28][29] Judgement under uncertainty favours safety and the only randomised controlled trial (RCT) that has examined screening for oral cancer used allied health providers, not GDPs, to undertake the screen. 28,30 The interviews from the Netherlands also highlight the need for rigorous evaluation of direct access.…”
Section: Discussionmentioning
confidence: 99%
“…22,25 There is evidence for the use of DCPs and clinicians other than GDPs to detect caries and to screen for oral cancer. [26][27][28][29] Judgement under uncertainty favours safety and the only randomised controlled trial (RCT) that has examined screening for oral cancer used allied health providers, not GDPs, to undertake the screen. 28,30 The interviews from the Netherlands also highlight the need for rigorous evaluation of direct access.…”
Section: Discussionmentioning
confidence: 99%
“…2). The reasons for this could be that in borderline cases where the periodontal pocket was close to the 3.5-mm threshold, H-Ts were inclined to report a positive index test result to ensure that nothing would be missed, a trend seen in other studies where, if in doubt, the patient is referred on for further investigation (Brocklehurst et al 2012). Alternatively, this may result from different judgment criteria being applied by GDPs and H-Ts when probing periodontal pockets (Velden and Vries 1980;Freed et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…This requires information on the expected sensitivity values of the new diagnostic test and the minimum acceptable lower confidence limit. Brocklehurst et al (2012) found that the sensitivity of different clinicians to assess photographs of potentially carious teeth was 85%. As clinicians were expected to find the judgment task in vivo easier, this was set at 90%.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…5,6 This raises a question about the rationale of using the most expensive resource (the GDP) to undertake this task, when other members of the dental team could be used safely, for example, dental hygienist-therapists (HTs). [7][8][9][10][11][12][13][14][15][16] Such an approach has the potential to release resources at a practice level and also increase the capacity to care for those who currently don't access services, thereby reducing the efficiency, cost-effectiveness and equity of NHS service provision. 5,17 HTs also adopt a more preventive approach, when compared to many GDPs, as their clinical training focuses on prevention rather than surgical intervention.…”
mentioning
confidence: 99%